Analisis Produksi Alkali Treated Cotoni Chips (ATCC) dan Alkali Treated Soinosum Chips (ATSC) Pada PT. Inti Nusa Raya Indonesia di Kabupaten Bombana - Nila Nila; Ine Fausayana; La Ode Kasno Arif (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
This research is motivated by the author's observations regarding the production of ATCC and ATSC. This study aims to determine the production process and the amount of ATCC and ATSC production at PT. Inti Nusa Raya Indonesia in Bombana Regency. This research was conducted at PT. Inti Nusa Raya Indonesia in Bombana Regency from October to December 2021. The data analysis used in this study is a quantitative descriptive analysis technique. The population in this study is PT. Inti Nusa Raya Indonesia until this research was carried out. Determination of informants in this study using purposive sampling technique by directly appointing respondents to be interviewed. The informants in this study are the production manager of PT. The core of Nusa Raya Indonesia. The type of data used in this research is quantitative data. This study's results indicate the production process of ATSC and ATSC at PT. Inti Nusa Raya Indonesia is carried out mechanically and carried out in several stages, namely the process of receiving raw materials, weighing, sorting, sifting, soaking, draining, washing, drying, cutting, chip cleaning, mixing, packaging, labeling, final storage and final loading of the product. . The results showed that in the production process of ATSC and ATSC, the raw material of seaweed used was 45 days of harvest to get the appropriate quality of carrageenan and good gel strength. While the concentration of KOH and NaOH used was 7-8% with a temperature of 70-80 c and cooked for 3 hours, drying time was 3-4 days when the weather was sunny and 7-10 days when the weather was cloudy.